On Harmonic Meromorphic Functions Associated with Basic Hypergeometric Functions - Huda Al dweby; Maslina Darus (The Scientific World Journal, 2013)
By making use of basic hypergeometric functions, a class of complex harmonic meromorphic functions with positive coefficients is introduced. We obtain some properties such as coefficient inequality, growth theorems, and extreme points.